EDUKASI PEMANFAATAN OLAHAN MAKROALGA HASIL BUDIDAYA DI DESA FUAFUNI KABUPATEN ROTE NDAO - Yuliana Salosso; Wesly Pasaribu; Asriati Djonu; Immaria Fransira (Jurnal Abdi Insani, 2025)
Rote Ndao Regency is one of the regions with the highest seaweed production in East Nusa Tenggara Province (NTT). This potential not only plays an important role in supporting the coastal economy, but also has great opportunities to improve the nutritional status and living standards of the people in the region. Seaweed is known as a highly nutritious food source that is beneficial to health. However, seaweed consumption levels are still low and there is a lack of innovation in seaweed processing. Therefore, this activity aims to increase community knowledge and awareness of the nutritional benefits of macroalgae and to develop innovative macroalgae-based processed products that have economic added value. This activity is divided into three stages. The first stage, preparation, was carried out to identify the problems faced by the community and determine the appropriate solutions. The second stage was the implementation of activities based on the results of the identification, including three main activities, namely counseling on the nutritional value of macroalgae, training on product diversification, and promotional counseling through online media. The entire series of activities ran well and received high enthusiasm from the participants. In addition, there has been an increase in community knowledge and skills in utilizing macroalgae as a source of nutrition and in making cendol and seaweed ice cream. The survey results show that 87.5% of the community is very satisfied with this community service activity. It is hoped that this activity can be a first step in encouraging the use of macroalgae as a source of nutritious food with high economic value.